Polymerase II–Associated Factor 1 Complex-Regulated FLOWERING LOCUS C-Clade Genes Repress Flowering in Response to Chilling - Nasim, Zeeshan; Susila, Hendry; Jin, Suhyun; Youn, Geummin; Ahn, Ji Hoon (Frontiers in Plant Science, 2022)
RNA polymerase II–associated factor 1 complex (PAF1C) regulates the transition from the vegetative to the reproductive phase primarily by modulating the expression of FLOWERING LOCUS C (FLC) and FLOWERING LOCUS M (FLM, also known as MADS AFFECTING FLOWERING1 [MAF1]) at standard growth temperatures. However, the role of PAF1C in the regulation of flowering time at chilling temperatures (i.e., cold temperatures that are above freezing) and whether PAF1C affects other FLC-clade genes (MAF2–MAF5) remain unknown. Here, we showed that Arabidopsis thaliana mutants of any of the six known genes that encode components of PAF1C (PLANT HOMOLOGOUS TO PARAFIBROMIN/CELL DIVISION CYCLE73, VERNALIZATION INDEPENDENCE2 [VIP2]/EARLY FLOWERING7 [ELF7], VIP3, VIP4, VIP5, and VIP6/ELF8) showed temperature-insensitive early flowering across a broad temperature range (10–27°C). Flowering of PAF1C-deficient mutants at 10°C was even earlier than that in flc, flm, and flc flm mutants, suggesting that PAF1C regulates additional factors. Indeed, RNA sequencing of PAF1C-deficient mutants revealed downregulation of MAF2–MAF5 in addition to FLC and FLM at both 10°C and 23°C. Consistent with the reduced expression of FLC and the FLC-clade members FLM/MAF1 and MAF2–MAF5, chromatin immunoprecipitation-quantitative PCR assays showed reduced levels of the permissive epigenetic modification H3K4me3 and increased levels of the repressive modification H3K27me3 at their chromatin. Knocking down MAF2–MAF5 using artificial microRNAs in the flc flm background (35S::amiR-MAF2–5 flc flm) resulted in significantly earlier flowering than flc flm mutants and even earlier than short vegetative phase (svp) mutants at 10°C. Wild-type seedlings showed higher accumulation of FLC and FLC-clade gene transcripts at 10°C compared to 23°C. Our yeast two-hybrid assays and in vivo coimmunoprecipitation analyses revealed that MAF2–MAF5 directly interact with the prominent floral repressor SVP. Late flowering caused by SVP overexpression was almost completely suppressed by the elf7 mutation, suggesting that SVP-mediated floral repression required a functional PAF1C. Taken together, our results showed that PAF1C regulates the transcription of FLC and FLC-clade genes to modulate temperature-responsive flowering at a broad range of temperatures and that the interaction between SVP and these FLC-clade proteins is important for floral repression.